Selective oxidation of cyclopentene to glutaraldehyde over the WO3/SiO2 catalyst - Lu, G.; Li, Xin Yong; Qu, Z.; Wang, Y.; Chen, G. (Elsevier BV North-Holland, 2008)
The WO3/SiO2 catalyst was prepared by sonication-impregnation combination approach using commercial silica gel as support. Influences of various factors on the yield of glutaraldehyde, such as WO3 loading and calcination temperature, were investigated and discussed in terms of the characterizations results of BET, XRD, Raman, FT-IR and XPS. It was found that the yield of glutaraldehyde increased rapidly with increase of WO3 loadings and calcination temperatures while WO3 was in the amorphous state, which reached the maximum value when amorphous WO3 started transforming into the crystalline form. Whereas, the yield of glutaradehyde decreased with further increase of WO3 loadings and calcination temperatures while WO3 has already transformed into the crystalline form. It is concluded that the formation of crystalline WO3 species and the interaction of WO3 with SiO2 play a key role for improving the activity of the WO3/SiO2 catalyst. © 2008 Elsevier B.V. All rights reserved.